Burnout Differences Between Critical Care and Inpatient Nurses: A Cross-sectional Study - Suwardianto, Heru; Doku, John Foster Atta; Ferede , Abebaw Jember (Lembaga Chakra Brahmanda Lentera (Chakra Brahmanda Lentera Institute) [CANDLE], 2025)
Background: Burnout is a common occupational risk among nurses, affecting well-being and patient care. However, limited evidence from low- and middle-income settings compares burnout across different clinical units. The extent of variation between Critical Care and Adult Inpatient Units remains unclear. This study therefore aimed to measure and compare burnout levels between nurses in these two settings and examine their implications for staff well-being and care quality. Methods: A cross-sectional study was conducted and reported in accordance with the STROBE guidelines. A purposive sampling technique was used to recruit 97 nurses (21 from Critical Care Units and 76 from Adult Inpatient Units). Inclusion criteria were registered nurses with ≥6 months of experience in their assigned unit, while nurses on extended leave or undergoing training were excluded. The independent variable was the clinical unit type, and the dependent variable was burnout. Burnout was assessed using the validated Maslach Burnout Inventory (MBI), which measures emotional exhaustion, depersonalization, and reduced personal accomplishment. Data were collected through self-administered questionnaires under researcher supervision, and analyzed using descriptive statistics and the Mann–Whitney U test, with statistical significance set at p < 0.05. Result: Nurses in Adult Inpatient Units experienced higher levels of burnout, with 42.1% reporting moderate burnout and 5.3% high burnout, whereas nurses in Critical Care Units reported primarily low burnout (85.7%) and no high burnout. Emotional exhaustion was the most prominent dimension, followed by depersonalization and reduced personal accomplishment. The difference in burnout levels between units was statistically significant (U = 528.000, Z = -2.751, p = 0.006). Conclusion: Burnout is more pronounced among nurses in Adult Inpatient Units, which may compromise patient care quality, safety, and communication. Targeted interventions—including workload management, psychosocial support, and resilience training—are essential to mitigate burnout, enhance staff well-being, and improve patient outcomes.